2016
DOI: 10.7705/biomedica.v37i3.3394
|View full text |Cite
|
Sign up to set email alerts
|

Does the corticosteroid’s treatment during the pre and postnatal period affect the neurodevelopmental outcome of premature newborns?

Abstract: Contribución de los autores:Marita Lardón: diseño de la investigación, recolección de datos y escritura del manuscrito Jose Uberos: diseño de la investigación, análisis de datos y revisión crítica del contenido del manuscrito Eduardo Narbona: recolección de datos, interpretación de los resultados y revisión crítica del contenido del manuscrito ¿Afecta el tratamiento con corticoides en los periodos prenatal y posnatal el neurodesarrollo del recién nacido prematuro?Marita Lardón, José Uberos, Eduardo Narbona Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The adjusted and unadjusted findings were similar to those reported in another systematic review, which included data before 2000 and found that a single course of antenatal corticosteroids was associated with unadjusted reductions in cerebral palsy compared with nonexposure . The literature search for the previous review concluded in August 2014, and since this time a substantial amount of research has emerged, including 5 studies that we included in the present work. In addition, the previous review excluded 12 of 42 studies because their data could not undergo a meta-analysis, rather than considering the studies narratively as performed in the present study.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The adjusted and unadjusted findings were similar to those reported in another systematic review, which included data before 2000 and found that a single course of antenatal corticosteroids was associated with unadjusted reductions in cerebral palsy compared with nonexposure . The literature search for the previous review concluded in August 2014, and since this time a substantial amount of research has emerged, including 5 studies that we included in the present work. In addition, the previous review excluded 12 of 42 studies because their data could not undergo a meta-analysis, rather than considering the studies narratively as performed in the present study.…”
Section: Discussionsupporting
confidence: 81%
“…After excluding 4802 duplicate records, we screened 8577 titles and abstracts and assessed 342 full-text articles. A total of 30 cohort studies met the final inclusion criteria that, together, involved more than 1.25 million children who were at least 1 year of age when the outcomes were assessed (Table 1; eTable 1 in the Supplement); the justifications for excluding other important studies are provided in eAppendix 2 in the Supplement. Race and ethnicity categories were reported in 6 studies (eTable 1 in the Supplement).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations